2019
DOI: 10.31989/ffhd.v9i4.599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coordinated Probiotic/Prebiotic/Phytobiotic Supplementation on Microbiome Balance and Psychological Mood State in Healthy Stressed Adults

Abstract: Background Interest in and knowledge of the gut microbiome has increased exponentially in the past decade. This once overlooked component of the gastrointestinal tract is now implicated in multiple aspects of human health, including mental wellness (e.g. depression, anxiety, stress), metabolic (e.g. diabetes, obesity), neurologic (e.g. Alzheimer's, Parkinson's, Autism Spectrum Disorder), gastrointestinal (e.g. irritable bowel syndrome, Crohn's), and immunologic (e.g. inflammation, cancer), among others. Purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Other studies indicated that oral administration of selected probiotic bacteria may have beneficial effects in the treatment of gastrointestinal and psychological stress-related disorders ( 37 39 ). Recent human studies have shown that taking a dietary supplement containing probiotics, prebiotics, and phytobiotics (phytonutrients with gut-enhancing effects) improves beneficial gut bacteria and psychological well-being ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies indicated that oral administration of selected probiotic bacteria may have beneficial effects in the treatment of gastrointestinal and psychological stress-related disorders ( 37 39 ). Recent human studies have shown that taking a dietary supplement containing probiotics, prebiotics, and phytobiotics (phytonutrients with gut-enhancing effects) improves beneficial gut bacteria and psychological well-being ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Certain compound classes such as polyphenols and polysaccharides have been shown to have prebiotic effects. Terms such as flavobiotics and phytobiotics have been used to refer to phytochemical constituents conferring health benefits on the host by positively influencing the gut microbiome [ 257 , 258 ]. Furthermore, recently, it has been proposed that polyphenols act as duplibiotics, meaning that these phytoconstituents have a dual effect on the microbiome by exerting antimicrobial properties, similar to antibiotics, on one hand, and by acting as prebiotics, positively stimulating the growth of beneficial bacteria, on the other hand [ 259 ].…”
Section: Discussionmentioning
confidence: 99%
“…The best available herbal treatments for IBS include natural polyphenolic products extracted from Perilla frutescens, Aloe vera, Mentha piperita, Cynara scolymus, Acacia catechu, Camellia sinensis and polyphenol compounds such as isoflavones baicalin, anthocyanins and quercetin. Such natural polyphenolic products possess numerous anti-inflammatory and anti-oxidant effects, which help to improve the IBS symptoms and the QOL scores in the IBS patients [26,[36][37][38][39][40][41][42][43][44][45].…”
Section: Current Treatments Of Ibs and Their Adverse Effectsmentioning
confidence: 99%